The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2105/ajph.2021.306168
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cannabis for Harm Reduction Among People at High Risk for Overdose in Vancouver, Canada (2016–2018)

Abstract: Objectives. To characterize the prevalence and reasons for the use of cannabis as a strategy to reduce the harms arising from other substances. Methods. We drew data about recent cannabis use and intentions from 3 prospective cohort studies of marginalized people who use drugs based in Vancouver, Canada, from June 2016 to May 2018. The primary outcome was “use of cannabis for harm reduction,” defined as using cannabis for substitution for licit or illicit substances such as heroin or other opioids, cocaine, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Finally, we also observed a significantly higher prevalence of opioid frequency reduction among people who increased their cannabis use during the pandemic. Although the self-reported use of cannabis to reduce or stop the use of unregulated or nonprescribed opioids and stimulants has been documented across samples of medical cannabis patients (Lucas et al, 2013(Lucas et al, , 2016, people who use drugs (Mok et al, 2021), and a representative sample of the U.S. population (Ishida et al, 2019), we hesitate to interpret our finding as being consistent with these observations as our study did not capture information about the intention to reduce a secondary substance with cannabis.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, we also observed a significantly higher prevalence of opioid frequency reduction among people who increased their cannabis use during the pandemic. Although the self-reported use of cannabis to reduce or stop the use of unregulated or nonprescribed opioids and stimulants has been documented across samples of medical cannabis patients (Lucas et al, 2013(Lucas et al, , 2016, people who use drugs (Mok et al, 2021), and a representative sample of the U.S. population (Ishida et al, 2019), we hesitate to interpret our finding as being consistent with these observations as our study did not capture information about the intention to reduce a secondary substance with cannabis.…”
Section: Discussionmentioning
confidence: 74%
“… 5 , 6 Recent cohort studies revealed that individuals at high risk of overdose commonly substitute cannabis for more harmful drugs (e.g., stimulants and opioids) as a harm reduction strategy. 7 Further, individuals reporting difficulty accessing addiction treatment or who used substances with limited treatment options, such as methamphetamines, had a higher likelihood of using cannabis as a harm reduction strategy. 8 These findings highlight the potential harm-reducing impacts of cannabis among PWUD.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis is a green leafy plant that humans have used for millennia due to its psychoactive and medicinal properties. A growing body of literature has identified a potential role for cannabis in reducing the harms associated with using other substances, including alcohol, opioids and stimulants (Lucas et al, 2020; Mok et al, 2021; Scavone et al, 2013; Socías et al, 2017). Indeed, recent research indicates that cannabis use can potentially play a therapeutic role for many people who use drugs (PWUD), including those at high risk of drug‐related harms such as overdose.…”
Section: Introductionmentioning
confidence: 99%
“…Several small trials in individuals with opioid use disorder showed reduced opioid craving for up to a week following a three-day treatment regimen with CBD (Hurd et al, 2015(Hurd et al, , 2019Suzuki et al, 2022). However, despite the devastating toll of overdose and other consequences of the ongoing drug poisoning epidemic, the application of medical cannabis therapies as part of a harm-reduction approach and recovery strategy has encountered significant barriers (Belle-Isle et al, 2014;Lo et al, 2023;Lucas, 2017;Mok et al, 2021Mok et al, , 2022. The present perspective piece examines obstacles that have impeded the implementation of cannabinoid therapies in the context of problematic substance use and addiction services.…”
mentioning
confidence: 99%